2020
DOI: 10.1055/a-1150-2286
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Occult Cancer in Patients with Venous Thromboembolism: Past, Present, and Future

Abstract: A strong link between cancer and thrombosis has been well recognized. The occurrence of venous thromboembolism (VTE) can be the first clinical sign of an undiagnosed (i.e., occult) cancer. Cancer is more often diagnosed after unprovoked compared with provoked VTE events, with a reported risk in recent studies of around 5%. Extensive, imaging-based screening strategies to detect occult cancer after unprovoked VTE do not appear to have a clear clinical benefit compared with a more limited cancer screening. To id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…The situation could be much the same as after unprovoked venous thromboembolism. 3 Given the difference in perspectives, the current results are not directly comparable to previous studies that reported no sex differences in cancer as a predisposing factor for CVT. 4 , 5 Importantly, it appears there is no specific type of occult cancer to look for after a CVT.…”
contrasting
confidence: 99%
“…The situation could be much the same as after unprovoked venous thromboembolism. 3 Given the difference in perspectives, the current results are not directly comparable to previous studies that reported no sex differences in cancer as a predisposing factor for CVT. 4 , 5 Importantly, it appears there is no specific type of occult cancer to look for after a CVT.…”
contrasting
confidence: 99%
“…In the TEEs cohort, most of the patients developed TEEs before treatment. As in previous studies, suspicion of underlying cancer is frequently raised in patients with TEEs [ 17 ].…”
Section: Discussionmentioning
confidence: 86%
“…3 The simplest explanation for this association is the hypercoagulability induced by the inflammatory storm secondary to the activity due to cancer. 4 The incidence of neoplasia at 1 year after an embolic episode is estimated to be between 10% and 15% with the majority diagnosed during the first 6 months. 5 The main problem remains the etiological strategy to be carried out.…”
Section: Discussionmentioning
confidence: 99%